2011
DOI: 10.5858/arpa.2010-0652-cp
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characteristics of Mucinous (Colloid) Carcinoma of the Breast in Fine-Needle Aspirates: Observations From the College of American Pathologists Interlaboratory Comparison Program in Nongynecologic Cytopathology

Abstract: Context.—Mucinous breast carcinoma has characteristic cytologic features, but few studies exist that analyze the reproducibility of this diagnosis. Objective.—To analyze participants' diagnosis of mucinous carcinoma in breast fine-needle aspiration (FNA) slides distributed in an educational interlaboratory peer comparison program. Design.—Participant responses for FNA slides with a reference diagnosis of mucinous carcinoma, distributed between 2001–2008 in the College of American … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
(39 reference statements)
1
11
0
Order By: Relevance
“…MC is specific type of invasive ductal caricinoma. The cytologic features show tight clusters of bland looking cells with moderate cellularity in the mucinous background 13. SRC demonstrates mucin only in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…MC is specific type of invasive ductal caricinoma. The cytologic features show tight clusters of bland looking cells with moderate cellularity in the mucinous background 13. SRC demonstrates mucin only in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Such mistakes are avoidable by supplementary ICC, which is necessary in about 10-20% of cases to make an appropriate diagnosis [36]. It has also been shown that adenocarcinomas in FNAs of the breast are often misjudged as fibroadenomas [37] and that failure to diagnose Warthin tumors is common [31,38]. …”
Section: Discussionmentioning
confidence: 99%
“…Mucinous breast carcinoma is most often diagnosed in older patients, aged 55–60 and above [29, 16]. The characteristic feature of this type of cancer is that it can be diagnosed in relatively early stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node metastases are rarely seen clinically in this form of cancer. All the factors are linked with favourable prognosis [1, 2, 4, 5, 9, 10]. …”
Section: Introductionmentioning
confidence: 99%